Endocrine pancreas development and regeneration: noncanonical ideas from neural stem cell biology - Masjkur, Jimmy; Poser, Steven W.; Nikolakopoulou, Polyxeni; Chrousos, George; McKay, Ronald D.; Bornstein, Stefan R.; Jones, Peter M.; Androutsellis-Theotokis, Andreas (American Diabetes Association, 2016)
Loss of insulin-producing pancreatic islet β-cells is a hallmark of type 1 diabetes. Several experimental paradigms demonstrate that these cells can, in principle, be regenerated from multiple endogenous sources using signaling pathways that are also used during pancreas development. A thorough understanding of these pathways will provide improved opportunities for therapeutic intervention. It is now appreciated that signaling pathways should not be seen as “on” or “off” but that the degree of activity may result in wildly different cellular outcomes. In addition to the degree of operation of a signaling pathway, noncanonical branches also play important roles. Thus, a pathway, once considered as “off” or “low” may actually be highly operational but may be using noncanonical branches. Such branches are only now revealing themselves as new tools to assay them are being generated. A formidable source of noncanonical signal transduction concepts is neural stem cells because these cells appear to have acquired unusual signaling interpretations to allow them to maintain their unique dual properties (self-renewal and multipotency). We discuss how such findings from the neural field can provide a blueprint for the identification of new molecular mechanisms regulating pancreatic biology, with a focus on Notch, Hes/Hey, and hedgehog pathways.